ADHD as a circadian rhythm disorder: evidence and implications for chronotherapy - Luu, Brandon; Fabiano, Nicholas (Frontiers in Psychiatry, 2025)
Accumulating evidence indicates that circadian rhythm dysfunction is a clinically significant and highly prevalent phenotype in a substantial subgroup of individuals with Attention-Deficit/Hyperactivity Disorder (ADHD). This perspective synthesizes convergent lines of evidence demonstrating strong associations between ADHD and evening chronotype with phase-delayed biological markers. Sleep disturbances are profound: insomnia and sleep disturbances affect up to 80% of adults with ADHD and similarly up to 82% of children with ADHD, delayed sleep-wake timing occurs in up to 78%, and dim-light melatonin onset (DLMO) is delayed by approximately 45 minutes in children and 90 minutes in adults. These alterations coincide with blunted and delayed cortisol rhythms, reduced pineal volume, and attenuated peripheral clock-gene rhythms (BMAL1/PER2). Intervention studies demonstrate that the circadian phase can be successfully advanced in ADHD populations. Melatonin and bright light therapy has advanced DLMO in both children and adults with ADHD. Emerging data correlate phase advancement with ADHD symptom improvement, and winter trials suggest circadian preference shifts best predict symptom improvement. Sleep programs improve ADHD symptoms, sleep quality, and functioning in children. Exercise and multimodal protocols for evening chronotypes successfully advance circadian timing in non-ADHD populations and warrant investigation in ADHD. Based on this evidence, we propose a pragmatic, behavioral-first clinical pathway: routine screening for sleep/circadian disturbances; phenotypic characterization through chronotype assessment, sleep tracking, and DLMO when feasible; implementation of fixed wake times, morning bright light exposure, evening light restriction with screen hygiene, and regularized zeitgebers; and selective low-dose melatonin for confirmed or probable DLMO delays.